Administrative Responsibility of Military Personnel - Tikhaleva, Elena Yu (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article describes features of administrative responsibility of military personnel on the basis of analysis of the current legislation and judicial practice. The status of the military personnel as special subjects of administrative responsibility is investigated. The bodies authorized to carry out process on cases of administrative offence are discussed. The administrative penalties that can’t be applied to military personnel are defined. Selected problems of manufacture on аffairs about administrative offences committed by military personnel.